Clinical researchSurgical treatment of thoracic outlet syndrome: immediate and mid-term results - Bertoletti, Giovanni; Varroni, Alessandro; Capoccia, Laura; Ianni, Giulia; Genovese, Vincenzo; Rached, Hadi Abi; Napoli, Filippo; Praquin, Barbara; Massucci, Marco (Archives of Medical Science, 2007)
Introduction: We report the results from a consecutive series of patients treated by scalenectomy or cervical rib resection for clearly symptomatic or paucisymptomatic thoracic outlet syndrome (TOS) over a 6-year period. Material and methods: From September 1999 to August 2005, 14 surgical decompressions were performed in 12 patients with unremitting signs and symptoms of nerve or vascular compression at the thoracic outlet. The symptoms of TOS were due to involvement of the brachial plexus in 8 cases (57.1%). A sign of vascular obstruction could be detected in 10 cases (71.4%): in 6 cases (42.8%) the presentation was predominantly arterial (arm claudication, coldness, Raynaud’s phenomenon and distal embolisation) and in 4 cases (28.5%) was related to vein compression with congestion and swelling of the affected arm or vein thrombosis. Two patients presented as emergencies with critical upper limb ischaemia or distal vessel embolisation. Results: The median follow-up period was 28.2 months (range 8-78 months). Results were evaluated in terms of technical success, lack of complications (temporary or permanent plexus injury, temporary or permanent phrenic palsy), relief of symptoms. Outcome data were divided into immediate/perioperative and mid-term results. Perioperative results: There was no operative mortality. Technical success was achieved in all patients in excision of the fibrous band with scalenectomy and in cervical rib excision. Mid-term results: In 4 patients with venous symptoms complete relief was achieved in 75%. In all patients who experienced arterial complications we registered complete relief. In patients with neurological presentation we detected complete relief in 5 (62.5%), relief of some symptoms in 2 (25%) and no improvement in 1 (12.5%). Conclusions: Scalenectomy performed by a standard supraclavicular approach seems to allow relief in the majority of patients with symptoms of neurological, arterial or venous compression at the thoracic outlet. Nevertheless, we emphasize the importance of an objective method of evaluation and the necessity of a prolonged follow-up.